Medical Use of Long-term Extended-release Opioid Analgesics in Commercially Insured Adults in the United States - Young, Jessica C (Pain Med, 2019)
OBJECTIVES: We examined the proportion of patients initiating extended-release (ER) opioids who become long-term users and describe how pain-related diagnoses before initiation of opioid therapy vary between drugs and over time. METHODS: Using MarketScan (2006–2015), a US national commercial insurance database, we examined pain-related diagnoses in the 182-day baseline period before initiation of ER opioid therapy to characterize indications for opioid initiation. We report the proportion who became long-term users, the median length of opioid therapy, and the proportion with cancer and other noncancer chronic pain, by active ingredient. RESULTS: Among 1,077,566 adults initiating ER opioids, 31% became long-term users, with a median length of use of 209 days. The most common ER opioids prescribed were oxycodone (26%) and fentanyl (23%), and the most common noncancer pain diagnoses were back pain (65%) and arthritis (48%). Among all long-term users, 16% had a diagnosis of cancer. We found notable variation by drug. Eighteen percent of patients initiating drugs approved by the Food and Drug Administration >10 years ago had evidence of cancer during baseline compared with only 8% of patients who received newer drugs. CONCLUSIONS: In a national sample of adults with private insurance, back pain was the most common diagnosis preceding initiation of opioid therapy. Opioids that have been approved within the last 10 years were more frequently associated with musculoskeletal pains and less frequently associated with cancer. Amid increasing concerns regarding long-term opioid therapy, our findings provide context regarding the conditions for which long-term opioid therapy is prescribed.